Studi Literatur Penerapan Konsep dan Peran Manajemen pada Organisasi - Huda, Khoirul; Abdoe, Thorieq Al; Sari, Lia Agita; Wantika, Ayu (Jayapangus Press, 2024)
The concept of management is a crucial element for effective organizational management. This article discusses various management theories and approaches, including basic functions such as planning, organizing, directing, and controlling. This research uses literature studies or literature reviews. The information used in this study comes from previous research written in national and international online publications. The data collection procedure makes use of the standards set by the authors of each magazine. Finding problems for research, gathering relevant data about them, and examining some fundamental hypotheses related to them are the broad goals of literary studies. The results of this study highlight the evolution of management thinking from the classical era to the modern era, including the contributions of important figures and recent advances in management practice. The research also explores the application of management concepts in various industries and organizations, as well as the challenges managers face in a dynamic business environment. In addition, this study emphasizes the importance of adaptation and innovation in management practices to improve organizational performance. Thus, this research provides an in-depth insight into the fundamental concepts of management and their influence on management practices. Modern management is based on principles such as discipline, division of labor, authority and responsibility, unity of command, unity of direction, subordination of personal interests, fair wages, centralization, authority, order, justice, stability of positions, initiative, and the spirit of solidarity. These principles help management actions achieve organizational goals.